Single molecule multiplexed nanopore protein screening in human serum using aptamer modified DNA carriers. Issue 1 (December 2017) - Sze, Jasmine; Ivanov, Aleksandar; Cass, Anthony; Edel, Joshua
Abstract The capability to screen a range of proteins at the single-molecule level with enhanced selectivity in biological fluids has been in part a driving force in developing future diagnostic and therapeutic strategies. The combination of nanopore sensing and nucleic acid aptamer recognition comes close to this ideal due to the ease of multiplexing, without the need for expensive labelling methods or extensive sample pre-treatment. Here, we demonstrate a fully flexible, scalable and low-cost detection platform to sense multiple protein targets simultaneously by grafting specific sequences along the backbone of a double-stranded DNA carrier. Protein bound to the aptamer produces unique ionic current signatures which facilitates accurate target recognition. This powerful approach allows us to differentiate individual protein sizes via characteristic changes in the sub-peak current. Furthermore, we show that by using DNA carriers it is possible to perform single-molecule screening in human serum at ultra-low protein concentrations. It is still a challenge for current nanopore sensing methods to differentiate multiple analytes from complex biological material. Here, the authors graft nucleic acid aptamer sequences along the backbone of a double stranded DNA carrier for the detection of multiple protein targets in human serum.